The effect of using vegetable fat blend on some attributes of kashar cheese - Harun Kesenkaş; Nayil Dinkçia; A. Kemal Seçkinb; Özer Kinika; Siddik Gönç (Grasas y Aceites, 2009)
Kashar cheese was produced from whole milk (MF) or skim milk homogenized with a commercial vegetable fat blend (VF) by the traditional procedure. The resulting cheese was stored for 3 months at 5°C, and analyzed initially for its gross composition and cholesterol content. In addition, the proteolysis and lipolysis, organic acid content and fatty acid composition were studied during the ripening of the cheese. The replacement of milk fat with a vegetable fat blend mainly affected pH, total solids and cholesterol content in the initial composition of the cheese (P < 0.05). The acid degree value and tyrosine contents in both types of cheese increased throughout ripening and significant differences were found between the cheeses after only 30 days of ripening (P < 0.05). The organic acid concentrations of both cheeses changed during ripening (P < 0.05) except for citric and oxalic acids. MF cheese showed higher levels of citric, succinic and oxalic acids especially towards to the end of ripening. Palmitic acid was the dominant fatty acid in MF cheese while the most abundant fatty acids in VF cheese were palmitic and oleic acid. The higher unsaturated fatty acid composition of the VF cheese has attracted attention from the healthy food image point of view.